2000
DOI: 10.1038/35021093
|View full text |Cite
|
Sign up to set email alerts
|

Molecular portraits of human breast tumours

Abstract: Human breast tumours are diverse in their natural history and in their responsiveness to treatments. Variation in transcriptional programs accounts for much of the biological diversity of human cells and tumours. In each cell, signal transduction and regulatory systems transduce information from the cell's identity to its environmental status, thereby controlling the level of expression of every gene in the genome. Here we have characterized variation in gene expression patterns in a set of 65 surgical specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

239
10,866
16
337

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13,631 publications
(11,697 citation statements)
references
References 20 publications
239
10,866
16
337
Order By: Relevance
“…Moreover, NuclErbB-2 positivity was a significant independent predictor of poor survival in patients with MembErbB-2 overexpression. NuclErbB-2 also resulted a marker of lower overall survival in the subgroup of patients with tumors MembErbB-2+/ER-PR-, included in the ErbB-2-positive molecular subtype [23-25]. This latter finding for the first time highlights NuclErbB-2 presence as a molecular signature that might help to define two biologically distinct subsets of tumors within the ErbB-2-positive molecular subtype.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Moreover, NuclErbB-2 positivity was a significant independent predictor of poor survival in patients with MembErbB-2 overexpression. NuclErbB-2 also resulted a marker of lower overall survival in the subgroup of patients with tumors MembErbB-2+/ER-PR-, included in the ErbB-2-positive molecular subtype [23-25]. This latter finding for the first time highlights NuclErbB-2 presence as a molecular signature that might help to define two biologically distinct subsets of tumors within the ErbB-2-positive molecular subtype.…”
Section: Discussionmentioning
confidence: 79%
“…In addition, patients bearing tumors with both MembErbB-2 and NuclErbB-2 had worse OS compared with patients whose tumors showed only MembErbB-2 (Figure 2C). In the molecular classification of breast cancer, tumors which lack ER and PR and overexpress MembErbB-2 (MembErbB-2+/ER-PR-) (Table 7) have been included in the ErbB-2-positive molecular subtype, associated with poor outcome [23-25]. Here we observed a significantly lower OS in the subset of patients with MembErbB-2+/ER-PR-tumors expressing NuclErbB-2 as compared to those whose tumors lack NuclErbB-2 (Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…initially proposed a molecular classification for breast cancer. Using a cDNA microarray of 38 breast cancer cases, this group defined a list of intrinsic genes 27, 28. Moreover, a larger cohort of breast cancer patients revealed that the luminal subgroup may be divided into luminal A and B 29.…”
Section: Discussionmentioning
confidence: 99%
“…Human breast cancer is classified into ‘intrinsic subtypes’: luminal A, luminal B, basal, Claudin‐low, and HER2‐enriched based on gene expression profiles (Perou et al ., 2000; Prat and Perou, 2011; Sorlie et al ., 2001). This molecular stratification complements the pathological classifiers of breast cancer, namely estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2), and is preserved in the established human breast cancer cell lines (Holliday and Speirs, 2011; Parker et al ., 2009; Prat and Perou, 2011).…”
Section: Introductionmentioning
confidence: 99%